Long-term analysis of the NOA-04 randomized phase III trial of sequential radiochemotherapy of anaplastic glioma with PCV or temozolomide. Issue 11 (1st July 2016) - Wick, Wolfgang; Roth, Patrick; Hartmann, Christian; Hau, Peter; Nakamura, Makoto; Stockhammer, Florian; Sabel, Michael C.; Wick, Antje; Koeppen, Susanne; Ketter, Ralf; Vajkoczy, Peter; Eyupoglu, Ilker; et al.
Abstract: Background: Optimal treatment and precise classification for anaplastic glioma are needed. Methods: The objective for long-term follow-up of NOA-04 is to optimize the treatment sequence for patients with anaplastic gliomas. Patients were randomized 2:1:1 to receive the standard radiotherapy (RT) (arm A), procarbazine, lomustine and vincristine (PCV) (arm B1), or temozolomide (TMZ) (arm B2). Results: Primary endpoint was time-to-treatment-failure (TTF), defined as progression after 2 lines of therapy or any time before if no further therapy was administered. Exploratory analyses examined associations of molecular marker status with TTF, progression-free survival (PFS), and overall survival (OS). At 9.5 (95% CI: 8.6–10.2) years, no difference between arms (A vs B1/B2) was observed: median TTF (4.6 [3.4–5.1] y vs 4.4 [3.3–5.3) y), PFS (2.5 [1.3–3.5] y vs 2.7 [1.9–3.2] y), and OS (8 [5.5–10.3] y vs 6.5 [5.4–8.3] y). Oligodendroglial versus astrocytic histology—but more so the subgroups according to CpG island methylator phenotype (CIMP) and 1p/19q co-deletion status—revealed a strong prognostic value of CIMP pos with (CIMP codel ) versus without 1p/19 co-deletion (CIMP non-codel ) versus CIMP neg . but no differential efficacy of RT versus chemotherapy for any of the endpoints. PFS was better for PCV- than for TMZ-treated patients with CIMP codel tumors (HR B1 vs B2 0.39 [0.17–0.92], P = .031). In CIMP neg . tumors, hypermethylation of the O6-methyl-guanyl-DNA methyltransferase promoter (MGMT) provided a risk reduction for PFS with chemotherapy. Conclusions: There is no differential activity of primary chemotherapy versus RT in any subgroup of anaplastic glioma. Molecular diagnosis is superior to histology. Trial Registration: clinicaltrials.gov Identifier: NCT00717210.